Protective Effects of Gintonin on Reactive Oxygen Species-Induced HT22 Cell Damages: Involvement of LPA1 Receptor-BDNF-AKT Signaling Pathway - Cho, Yeon-Jin; Choi, Sun-Hye; Lee, Ra-Mi; Cho, Han-Sung; Rhim, Hyewhon; Kim, Hyoung-Chun; Kim, Byung-Joo; Kim, Jong-Hoon; Nah, Seung-Yeol (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Gintonin is a kind of ginseng-derived glycolipoprotein that acts as an exogenous LPA receptor ligand. Gintonin has in vitro and in vivo neuroprotective effects; however, little is known about the cellular mechanisms underlying the neuroprotection. In the present study, we aimed to clarify how gintonin attenuates iodoacetic acid (IAA)-induced oxidative stress. The mouse hippocampal cell line HT22 was used. Gintonin treatment significantly attenuated IAA-induced reactive oxygen species (ROS) overproduction, ATP depletion, and cell death. However, treatment with Ki16425, an LPA1/3 receptor antagonist, suppressed the neuroprotective effects of gintonin. Gintonin elicited [Ca-2](i) transients in HT22 cells. Gintonin-mediated [Ca-2](i) transients through the LPA1 receptor-PLC-IP3 signaling pathway were coupled to increase both the expression and release of BDNF. The released BDNF activated the TrkB receptor. Induction of TrkB phosphorylation was further linked to Akt activation. Phosphorylated Akt reduced IAA-induced oxidative stress and increased cell survival. Our results indicate that gintonin attenuated IAA-induced oxidative stress in neuronal cells by activating the LPA1 receptor-BDNF-TrkB-Akt signaling pathway. One of the gintonin-mediated neuroprotective effects may be achieved via anti-oxidative stress in nervous systems.